Social Media Usage and Self-Esteem: The Case Study of TikTok Addiction among UTHM Diploma Students - Tuan Lokman, Tuan Nursafiah; Mohammad Hazli, Marina Nur Hidayah; Mohd Nasir, Mohammad Aiman; Juma'at, Nuramirah; Ahmad Nordin, Norain (Multidisciplinary Applied Research and Innovation, 2026)
TikTok is a short-form video app that provides a variety of content, from informative to entertaining, appealing to young people. TikTok’s algorithm constantly displays videos that are of interest to users, causing them to watch endlessly. This will lead to overuse, making users easily compare themselves to others, relying on external validation and tending to avoid reality. These characteristics can have a negative impact on psychological well-being, such as self-esteem. This study was conducted to identify the level of TikTok addiction and its relationships with self-esteem among diploma students at Universiti Tun Hussein Onn Malaysia. An online survey was used to collect data for this quantitative study, which included 215 diploma students. The Bergen Social Media Addiction Scale (BSMAS) was used to measure the level of social media addiction, and the Rosenberg Self-Esteem Scale (RSE) to assess self-esteem. Descriptive analysis and Spearman correlation were used in analyzing the data using SPSS software. The results of the descriptive analysis found that the average overall score for BSMAS was 16.93 from a score range of 6 to 30, while the average score for RSE was 26.53 from a score range of 10 to 40. This finding shows that students are at a moderate level in using TikTok, while their self-esteem levels are also at a moderate to high level. There was a significant negative relationship between TikTok addiction and self-esteem (r = -0.230, p < 0.01), which indicates that the higher the TikTok addiction, the lower the student’s self-esteem. This finding has important implications for the university in developing interventions to give awareness about the balance of social media use and the development of self-esteem among students.